Representasi Kesepian Ibu dalam Film Bila Esok Ibu Tiada melalui Pendekatan Semiotika Ferdinand de Saussure - Tiffania, Ni Kadek Ayusrine; Anggreswari, Ni Putu Yunita; Ramadiansyah, Sahri Aflah; Haes, Putri Ekaresty (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the phenomenon of a mother’s loneliness in the film Bila Esok Ibu Tiada through Ferdinand de Saussure’s semiotic perspective. The research employs a qualitative descriptive approach with textual and visual analysis of the film as the primary data. Saussure’s semiotics—particularly the relationship between signifier and signified, and the concept of langue and parole—are used to interpret the meanings embedded in the mother’s loneliness. The findings indicate that loneliness is represented through verbal and non-verbal signs, including dialogue, facial expressions, mise-en-scène, and cinematographic composition. The contrast between the mother’s domestic space and her emotional isolation illustrates the separation between social reality and inner experience. The study reveals that the film constructs loneliness not merely as an emotional condition but as a social discourse reflecting the marginalization of women’s roles in modern families. In conclusion, Saussurean semiotics provides a framework for understanding how cinematic language conveys complex meanings of maternal loneliness.